Economic Efficiency of Regular Rice Farming and Mina Padi Production Factors - Merliana, Alifa; Mulyatno Setiawan, Bambang; Budiraharjo, Kustopo (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol 15 No 3 (2021): Vol.15, No.3, 2021DO - 10.24843/SOCA.2021.v15.i03.p10, 2021)
Economic efficiency analysis is used to determine the level of efficiency from economic perspective. Economic efficiency analysis is carried out by determining the equivalence value between Marginal Product Value and Marginal Sacrifice Cost. The objectives of this research are analyzing the impact of the use of inputs on the resulting output, comparing the amount of production, analyzing economic efficiency, and calculating income. The location of this research was determined purposively. The method used in the sampling process was probability sampling with cluster random sampling technique. The number of samples was 60 respondents, consisting of 30 members from two different types of farming. The data analysis used was influence test, independent difference test, one sample t-test, multiple linear regression, economic efficiency analysis, and farm income. The results show that there is a simultaneous influence on the use of inputs on farm output. There is a partial effect of the use of land and seed inputs on output; however, fertilizers, the amount of labor, and variables have no effect. There is no difference in the yield obtained between regular rice farming and mina padi combined farming (A form of combined farming that utilizes stagnant water from the planted rice fields as a pond for fish cultivation that maximizes the yield of rice fields). Economic efficiency cannot be achieved in rice farming, as well as the use of production factors in mina padi. Rice farming produces a lower average income than mina padi.